2022
DOI: 10.1021/acsami.1c23840
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Self-assembly of Organics/MXene Hybrid Cathodes Toward High-Rate-Performance Sodium Ion Batteries

Abstract: Conjugated quinones are promising cathode materials for sodium-ion batteries. However, the contemporary primary conjugated quinones cathodes still hold to limited capacity, poor rate performance and low cyclability, due to the poor electronic and ionic conductivity. Herein, a series of high-performance conjugated-quinones@MXene hybrid cathodes is constructed by an in situ polymerization-assembly strategy based on the hydrogen bond and S−Ti interaction. The PAQS@Ti 3 C 2 T x MXene hybrid, as a typical example, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
2
12
0
Order By: Relevance
“…Recently, Gao and co‐workers achieved the in situ polymerization assembly of polyanthraquinone sulfide (PAQS) on Ti 3 C 2 T x multilayered MXene (PAQS@MXene) based on intermolecular interaction between functional groups in organic materials and surface functional groups on MXene ( Figure a). [ 182 ] The PAQS@MXene was prepared by stirring a mixture of MXene powders, dichloroanthraquinone, and sodium sulfide nonahydrate in NMP at 200 °C for 12 h. Theory and experiment revealed that PAQS@MXene had higher Na + diffusion coefficient, better electronic conductivity, and stronger Na + adsorption ability than bare PAQS. The PAQS@MXene cathode could still have a capacity of 174 mAh g −1 at 1.0 A g −1 after 450 cycles in SIBs.…”
Section: In Situ Growth Engineering On 2d Mxene For Rechargeable Batt...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gao and co‐workers achieved the in situ polymerization assembly of polyanthraquinone sulfide (PAQS) on Ti 3 C 2 T x multilayered MXene (PAQS@MXene) based on intermolecular interaction between functional groups in organic materials and surface functional groups on MXene ( Figure a). [ 182 ] The PAQS@MXene was prepared by stirring a mixture of MXene powders, dichloroanthraquinone, and sodium sulfide nonahydrate in NMP at 200 °C for 12 h. Theory and experiment revealed that PAQS@MXene had higher Na + diffusion coefficient, better electronic conductivity, and stronger Na + adsorption ability than bare PAQS. The PAQS@MXene cathode could still have a capacity of 174 mAh g −1 at 1.0 A g −1 after 450 cycles in SIBs.…”
Section: In Situ Growth Engineering On 2d Mxene For Rechargeable Batt...mentioning
confidence: 99%
“…Reproduced with permission. [ 182 ] Copyright 2022, American Chemical Society. b) Schematic showing the fabrication process of TAP/Ti 3 C 2 T x .…”
Section: In Situ Growth Engineering On 2d Mxene For Rechargeable Batt...mentioning
confidence: 99%
“…The major advantages of in situ polymerization-assembly strategy are higher organic material loading and better organic-inorganic interface. Based on it, we fabricated PAQS@Ti 3 C 2 T x MXene hybrid with the polymer weight content of about 77 % via hydrogen bond and SÀ Ti interaction, [90] as described in as Figure 8. The hybrid showed typical sandwiched structure with intimate organic-inorganic contact that facilitated electrons/ions transport.…”
Section: Organics/mxene Composites As Cathode Materialsmentioning
confidence: 99%
“…Nowadays, significant population growth and economic expansion in the 21st century enhance the steep consumption of fossil fuels, exacerbating the energy crisis and motivating many academicians to develop high-efficiency energy storage . Because of the high energy storage density, both lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) have sparked the interest of a growing number of individuals over the past three decades. However, because the ionic radius of sodium (∼1.02 Å) is greater than that of lithium (∼0.76 Å), most anode materials for LIBs are not ideal for SIBs …”
Section: Introductionmentioning
confidence: 99%
“…2−4 However, because the ionic radius of sodium (∼1.02 Å) is greater than that of lithium (∼0.76 Å), most anode materials for LIBs are not ideal for SIBs. 5 Recently, MXene, an emerging family of two-dimensional (2D) metal carbide/nitride, has received considerable attention in energy storage after being discovered by Gogotsi and coworkers. 6,7 Particularly, Ti 3 C 2 T x MXene with surface hydrophilicity, superior electrical conductivity, and outstanding structural stability is a prospective candidate electrode in both LIBs and SIBs.…”
Section: Introductionmentioning
confidence: 99%